Additive manufacturing material anisotropy degree calculation and evaluation method and system
Through ion irradiation and nanoindentation testing, the anisotropy factor of additive manufacturing materials was calculated, which solved the problem of difficulty in quantitatively evaluating the anisotropy of additive manufacturing materials in the prior art, and achieved efficient quantification of SLM molded materials evaluate.
Patent Information
- Application Number
- CN202411258598.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The prior art lacks an evaluation method for quantitatively characterizing the anisotropy of additive manufacturing materials, especially in SLM-shaped nickel-based alloys, where the anisotropy effect is masked by process defects and is difficult to obtain through macroscopic mechanical testing.
By preparing the original sample, selecting some samples for ion irradiation, obtaining the irradiated sample, and then performing nanoindentation tests, extracting the characteristic nanohardness values, and calculating the relative irradiation hardening rate of different orientation surfaces and the relative irradiation hardening rate of the deposition surfaces. , and finally, based on these rates, the anisotropy factor of the hardening effect is calculated to evaluate the anisotropy degree of the material.
Quantitative evaluation of the degree of anisotropy of additive manufacturing materials has been achieved. It is suitable for small batch materials or workpieces formed by SLM additive manufacturing, which helps to guide and optimize related material additive process technologies.
Smart Images

Figure CN119437829A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to metal additive manufacturing, and more specifically, to a method and system for calculating and evaluating the degree of anisotropy of additive manufacturing materials. Background Art
[0002] Metal Additive Manufacturing (Additive Manufacturing) is a metal or alloy preparation process that accumulates materials layer by layer. It has the advantages of high design freedom, high material utilization, and convenient and efficient production. Among them, Selective Laser Melted (SLM) is one of the more mature processes in metal additive manufacturing. Through high-precision laser scanning and energy control, parts can be quickly formed to obtain better material properties than traditional manufacturing. It is currently widely used in industrial fields such as aerospace, transportation, and precision medicine.
[0003] As an important energy industry, nuclear power has strict considerations on the safety of materials used. The development and application of metal additive manufacturing in the field of nuclear power is currently in its early stages. At present, it has only been applied to some frequently replaced and non-critical components such as some loop filters and fuel assembly base frames. The research on the cultivation and manufacturing of metal materials and components is mainly in the aspects of forming process and basic performance evaluation. Due to its special forming method, its organizational structure must have certain anisotropy compared with the traditional forging method. Anisotropy in a broad sense refers to the difference in performance of materials in all directions, which is mainly caused by the organizational morphology of the material, such as the columnar crystal structure of cast metal and the columnar crystal structure produced by additive manufacturing. Most of the alloys obtained by SLM additive manufacturing will produce a temperature gradient parallel to the printing direction due to the temperature field of the layer molten pool, so a certain form of columnar crystal structure is produced. The columnar crystal morphology is closely related to the printing material, printing process, etc. Research often characterizes the anisotropy of additive manufacturing materials through mechanical tensile properties, that is, comparing the difference in mechanical properties in the vertical (printing direction) and transverse directions. However, different research results show that the anisotropy of the same material after printing is different under different equipment and process parameters, and there is currently no quantitative evaluation method to characterize the anisotropy of additive materials. The use of mechanical tensile performance parameter comparison requires a larger sample size, which is difficult to achieve for additive manufacturing of small batches of products. For nickel-based alloys commonly used in industry (such as 718 alloy), due to their excellent high-temperature performance, the size of columnar crystals obtained by SLM molding is relatively small. The anisotropic effect brought by the columnar crystals will be masked by the performance changes caused by the process defects in SLM molding, making it more difficult to obtain the anisotropy of the columnar crystal structure in macroscopic mechanical tests. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method and system for calculating and evaluating the degree of anisotropy of additive manufacturing materials in view of the problems existing in the prior art.
[0005] The technical solution adopted by the present invention to solve the technical problem is: constructing a method for calculating and evaluating the degree of anisotropy of additive manufacturing materials, comprising the following steps:
[0006] Prepare an original sample based on an object to be evaluated; the object to be evaluated is an additively manufactured nickel-based 718 alloy;
[0007] Selecting a portion of the original sample for irradiation to obtain an irradiated sample;
[0008] Performing nanoindentation tests on non-irradiated samples and irradiated samples to obtain a relationship curve between indentation depth and nanohardness; the non-irradiated samples are samples of the original samples that have not been irradiated;
[0009] Extract characteristic nanohardness values based on the relationship curve between the indentation depth and the nanohardness to obtain characteristic nanohardness values;
[0010] Calculating according to the characteristic nanohardness value, obtaining the relative radiation hardening rate of the surfaces with different orientations;
[0011] Calculating according to the characteristic nanohardness values, obtaining relative radiation hardening rates of different deposition surfaces;
[0012] Calculating according to the relative radiation hardening rates of the different oriented surfaces and the relative radiation hardening rates of the different deposition surfaces to obtain an anisotropy degree factor of the hardening effect;
[0013] The anisotropy degree of the object to be evaluated is evaluated based on the anisotropy degree factor.
[0014] In the method for calculating and evaluating the anisotropy degree of additive manufacturing materials described in the present invention, preparing an original sample based on the object to be evaluated includes:
[0015] The object to be evaluated is subjected to wire cutting processing according to different orientation surfaces and deposition surfaces to obtain square sheet samples;
[0016] The surface of the square plate sample is ground and polished to obtain the original sample.
[0017] In the method for calculating and evaluating the degree of anisotropy of additively manufactured materials described in the present invention, the step of selecting a portion of the original samples for irradiation to obtain irradiated samples comprises:
[0018] Selecting some samples from the original sample;
[0019] The polished surfaces of the partial samples are subjected to ion irradiation to obtain the irradiated samples.
[0020] In the method for calculating and evaluating the degree of anisotropy of additive manufacturing materials described in the present invention, the maximum depth of ion irradiation damage of the irradiated sample is 1 μm to 1.5 μm, the irradiation operation amount is 1.0 dpa, and the irradiation temperature is room temperature.
[0021] In the method for calculating and evaluating the degree of anisotropy of additively manufactured materials described in the present invention, the nanoindentation test is performed on the non-irradiated sample and the irradiated sample to obtain the relationship curve between the indentation depth and the nanohardness, which includes:
[0022] The non-irradiated sample and the irradiated sample are subjected to a nanoindentation test in a continuous stiffness mode to obtain a relationship curve between the indentation depth and the nanohardness.
[0023] In the method for calculating and evaluating the degree of anisotropy of additive manufacturing materials described in the present invention, the test conditions of the nanoindentation test are: Poisson's ratio is 0.3, the indentation depth is 2 μm, and the number of test points for each sample is not greater than or equal to 10.
[0024] In the method for calculating and evaluating the degree of anisotropy of additively manufactured materials described in the present invention, the characteristic nanohardness value is extracted based on the relationship curve between the indentation depth and the nanohardness to obtain the characteristic nanohardness value, which includes:
[0025] Based on the relationship curve between the indentation depth and the nanohardness, a relationship curve of the segmented slope is obtained;
[0026] Determine the first selected area;
[0027] Performing linear fitting on the relationship curve of the segmented slopes based on the first selected area to obtain a first fitting straight line;
[0028] Calculating the arithmetic square root of the intercept of the first fitting straight line to obtain the hardness of the substrate;
[0029] Determine the second choice area;
[0030] Performing linear fitting on the relationship curve of the segmented slopes based on the second selected area to obtain a second fitting straight line;
[0031] Calculating the arithmetic square root of the intercept of the second fitting straight line to obtain the hardness of the surface;
[0032] The hardness of the substrate and the hardness of the surface are the characteristic nanohardness values.
[0033] In the method for calculating and evaluating the degree of anisotropy of additively manufactured materials described in the present invention, the characteristic nanohardness values include: the hardness of the substrate and the hardness of the surface;
[0034] The hardness of the substrate includes: the substrate hardness of the unirradiated samples of the scanning surface A series, the substrate hardness of the irradiated samples of the scanning surface A system, the substrate hardness of the unirradiated samples of the deposition surface B series, and the substrate hardness of the irradiated samples of the deposition surface B system;
[0035] The surface hardness includes: the surface hardness of the unirradiated samples of the scanning surface A series, the surface hardness of the irradiated samples of the scanning surface A system, the surface hardness of the unirradiated samples of the deposition surface B series, and the surface hardness of the irradiated samples of the deposition surface B system.
[0036] In the method for calculating and evaluating the degree of anisotropy of additively manufactured materials described in the present invention, the step of calculating according to the characteristic nanohardness value to obtain the relative radiation hardening rate of different oriented surfaces includes:
[0037] Calculating according to the surface hardness of the unirradiated samples of the scanning surface A series and the matrix hardness of the unirradiated samples of the scanning surface A series, to obtain the hardness difference rate between the surface and the matrix of the unirradiated samples of the scanning surface A series;
[0038] Calculate the hardness difference between the surface and the substrate of the irradiated samples on the scanning surface A series according to the surface hardness of the irradiated samples on the scanning surface A series and the substrate hardness of the irradiated samples on the scanning surface A series to obtain the hardness difference between the surface and the substrate of the irradiated samples on the scanning surface A series;
[0039] The relative radiation hardening rate of the scanning surface series A is obtained by calculating the hardness difference rate between the surface of the unirradiated sample and the substrate and the hardness difference rate between the surface of the irradiated sample and the substrate of the scanning surface series A; the relative radiation hardening rate of the scanning surface series A is the relative radiation hardening rate of the surfaces with different orientations;
[0040] The calculation according to the characteristic nanohardness value to obtain the relative radiation hardening rate of different deposition surfaces includes:
[0041] Calculate the hardness difference between the surface and the substrate of the non-irradiated samples of the deposition surface B series according to the surface hardness of the non-irradiated samples of the deposition surface B series and the substrate hardness of the non-irradiated samples of the deposition surface B series to obtain;
[0042] Calculate the hardness difference between the surface and substrate of the B series irradiated samples on the deposition surface according to the surface hardness of the B series irradiated samples on the deposition surface and the substrate hardness of the B series irradiated samples on the deposition surface to obtain the hardness difference between the surface and substrate of the B series irradiated samples on the deposition surface;
[0043] The relative irradiation hardening rate of the deposition surface series B is obtained by calculating the hardness difference rate between the surface of the non-irradiated samples of the deposition surface series B and the substrate and the hardness difference rate between the surface of the irradiated samples of the deposition surface series B and the substrate;
[0044] The relative radiation hardening rates of the deposition surfaces B series are the relative radiation hardening rates of the different deposition surfaces.
[0045] The present invention also provides a system for calculating and evaluating the anisotropy degree of additive manufacturing materials, comprising:
[0046] A sample preparation unit, used for preparing an original sample based on an object to be evaluated; the object to be evaluated is a sample of an additively manufactured nickel-based 718 alloy;
[0047] An irradiation unit, used for selecting a portion of the original sample for irradiation to obtain an irradiated sample;
[0048] A nanoindentation test unit, used to perform nanoindentation test on non-irradiated samples and irradiated samples to obtain a relationship curve between indentation depth and nanohardness; the non-irradiated samples are samples of the original samples that have not been irradiated;
[0049] A characteristic value extraction unit, used to extract characteristic nanohardness values based on the relationship curve between the indentation depth and the nanohardness, and obtain characteristic nanohardness values;
[0050] A first hardening rate calculation unit, used to calculate according to the characteristic nanohardness value to obtain relative radiation hardening rates of surfaces with different orientations;
[0051] A second hardening rate calculation unit, used to calculate according to the characteristic nanohardness value to obtain relative radiation hardening rates of different deposition surfaces;
[0052] an anisotropy degree factor calculation unit, used to calculate according to the relative radiation hardening rates of the different orientation surfaces and the relative radiation hardening rates of the different deposition surfaces to obtain the anisotropy degree factor of the hardening effect;
[0053] The anisotropy program evaluation unit is used to evaluate the anisotropy degree of the object to be evaluated based on the anisotropy degree factor.
[0054] The method and system for calculating and evaluating the degree of anisotropy of additive manufacturing materials implemented in the present invention have the following beneficial effects: including: preparing original samples based on the object to be evaluated; selecting some samples in the original samples for irradiation to obtain irradiated samples; performing nanoindentation tests on non-irradiated samples and irradiated samples to obtain the relationship curve between indentation depth and nanohardness; extracting characteristic nanohardness values; calculating based on the characteristic nanohardness values to obtain the relative irradiation hardening rates of different oriented surfaces and the relative irradiation hardening rates of different deposition surfaces; calculating based on the relative irradiation hardening rates of different oriented surfaces and the relative irradiation hardening rates of different deposition surfaces to obtain the anisotropy degree factor of the hardening effect; evaluating the degree of anisotropy of the object to be evaluated based on the anisotropy degree factor. The present invention is more suitable for small batches of materials or workpieces formed by SLM additive manufacturing, and can quantitatively evaluate anisotropy, which is helpful to guide and optimize the additive process technology of related materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0056] Figure 1 It is a schematic flow chart of a method for calculating and evaluating the degree of anisotropy of additive manufacturing materials provided by the present invention;
[0057] Figure 2 It is a principle block diagram of the anisotropy degree calculation and evaluation system of additive manufacturing materials provided by the present invention;
[0058] Figure 3 It is a dH relationship diagram before and after ion irradiation of different orientation surfaces provided by the present invention;
[0059] Figure 4 It is the 1 / dH before and after ion irradiation of different orientation surfaces provided by the present invention. 2 Relationship diagram. DETAILED DESCRIPTION
[0060] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] refer to Figure 1 , Figure 1 A schematic flow chart of the method for calculating and evaluating the degree of anisotropy of additive manufacturing materials provided by the present invention.
[0062] Specifically, Figure 1 As shown, the method for calculating and evaluating the anisotropy degree of additive manufacturing materials includes the following steps:
[0063] Step S101: preparing an original sample based on an object to be evaluated.
[0064] Among them, the object to be evaluated is the additively manufactured nickel-based 718 alloy.
[0065] In an embodiment of the present invention, preparing an original sample based on the object to be evaluated includes: performing wire cutting processing on the object to be evaluated according to different orientation surfaces and deposition surfaces to obtain a square sheet sample; and grinding and polishing the surface of the square sheet sample to obtain an original sample.
[0066] Specifically, a certain additively manufactured nickel-based 718 material is processed into square sheet samples with a thickness of 1 mm and a side length of 5 to 10 mm by wire cutting according to different orientation surfaces (i.e., scanning surface (A series)) and deposition surface (B series). The sample surface is polished with 400 to 2000# metallographic sandpaper, and then the mirror surface is polished.
[0067] Step S102: Select some samples from the original samples for irradiation to obtain irradiated samples.
[0068] In an embodiment of the present invention, selecting some samples from the original samples for irradiation to obtain irradiated samples includes: selecting some samples from the original samples; ion irradiating the polished surfaces of some samples to obtain irradiated samples. The maximum depth of ion irradiation damage of the irradiated samples is 1 μm to 1.5 μm, the irradiation operation amount is 1.0 dpa, and the irradiation temperature is room temperature.
[0069] Optionally, in an embodiment of the present invention, the number of original samples can be selected and determined according to actual needs. For example, two original samples can be prepared, and correspondingly, the partial sample can be any one of the original samples, that is, the irradiated sample is one, and accordingly, the remaining sample in the original sample is one, which is the subsequent non-irradiated sample.
[0070] Specifically, a sample is selected from the original samples for ion irradiation experiment, and an irradiation experiment is carried out on its polished surface. The maximum depth of ion irradiation damage is 1 μm to 1.5 μm, the irradiation operation amount is 1.0 dpa, and the irradiation temperature is room temperature.
[0071] Step S103: Perform nanoindentation test on the non-irradiated sample and the irradiated sample to obtain a relationship curve between the indentation depth and the nanohardness, wherein the non-irradiated sample is a sample that has not been irradiated in the original sample.
[0072] In the embodiment of the present invention, performing nanoindentation test on the non-irradiated sample and the irradiated sample to obtain the relationship curve between the indentation depth and the nanohardness includes: performing nanoindentation test in a continuous stiffness mode on the non-irradiated sample and the irradiated sample to obtain the relationship curve between the indentation depth and the nanohardness. The test conditions of the nanoindentation test are: Poisson's ratio is 0.3, the indentation depth is 2 μm, and the number of test points for each sample is not greater than or equal to 10.
[0073] Specifically, continuous stiffness mode nanoindentation tests were carried out on unirradiated samples and irradiated samples, with a Poisson's ratio of 0.3 and an indentation depth of 2 μm. There were no less than 10 test points for each sample, and the average curve of the relationship between "indentation depth (nm), d" and "nanohardness (GPa), H" of the corresponding samples was obtained, that is, the indentation depth and nanohardness relationship curve (dH relationship curve).
[0074] Step S104: extracting characteristic nanohardness values based on the relationship curve between the indentation depth and the nanohardness to obtain characteristic nanohardness values.
[0075] In the embodiment of the present invention, the characteristic nanohardness value is extracted based on the relationship curve between the indentation depth and the nanohardness, and the characteristic nanohardness value is obtained by: drawing a graph based on the relationship curve between the indentation depth and the nanohardness to obtain a relationship curve of the segmented slope; determining a first selected area; performing a linear fit on the relationship curve of the segmented slope based on the first selected area to obtain a first fitting straight line; calculating the arithmetic square root of the intercept of the first fitting straight line to obtain the hardness of the substrate; determining a second selected area; performing a linear fit on the relationship curve of the segmented slope based on the second selected area to obtain a second fitting straight line; calculating the arithmetic square root of the intercept of the second fitting straight line to obtain the hardness of the surface; the hardness of the substrate and the hardness of the surface are the characteristic nanohardness values. Wherein, the first selected area is 0μm -1 ≤1 / d≤1μm -1 The second selected area is 4μm -1 ≤1 / d≤10μm -1 area.
[0076] In the embodiment of the present invention, the characteristic nanohardness value includes: the hardness of the substrate and the hardness of the surface; the hardness of the substrate includes: the substrate hardness of the scanning surface A series of unirradiated samples, the substrate hardness of the scanning surface A system irradiated samples, the substrate hardness of the deposition surface B series of unirradiated samples and the substrate hardness of the deposition surface B system irradiated samples; the surface hardness includes: the surface hardness of the scanning surface A series of unirradiated samples, the surface hardness of the scanning surface A system irradiated samples, the surface hardness of the deposition surface B series of unirradiated samples and the surface hardness of the deposition surface B system irradiated samples.
[0077] Specifically, according to the obtained dH relationship curve, 1 / d(μm-1 ) and H 2 (GPa 2 ) to obtain a segmented slope relationship curve, select 0μm -1 ≤1 / d≤1μm -1 Linear fitting is performed on the area of the fitting line, and the square root H0 of the intercept of the fitting line is calculated to obtain the hardness of the matrix; 4μm is selected -1 ≤1 / d≤10μm -1 Linear fitting is performed on the area of , and the square root H1 of the intercept of the fitting line is calculated to obtain the surface hardness. According to this step, the calculation results are:
[0078] Scanning surface A series non-irradiated sample matrix hardness: H A0,unirr ;
[0079] Scanning surface A series unirradiated sample surface hardness: H A1,unirr ;
[0080] Scanning surface A series irradiated sample matrix hardness: H A0,irr ;
[0081] Scanning surface A series irradiated sample surface hardness: H A1,irr ;
[0082] Deposition surface B series non-irradiated sample matrix hardness: H B0,unirr ;
[0083] Surface hardness of unirradiated samples of series B on the deposition surface: H B1,unirr ;
[0084] Deposition surface B series irradiated sample matrix hardness: H B0,irr ;
[0085] Surface hardness of B series irradiated samples on the deposition surface: H B1,irr .
[0086] Step S105: Calculate according to the characteristic nanohardness value to obtain the relative radiation hardening rate of the surfaces with different orientations.
[0087] In the embodiment of the present invention, the relative radiation hardening rate of different oriented surfaces is obtained by calculating according to the characteristic nanohardness value, including: calculating according to the surface hardness of the unirradiated samples of the scanning surface A series and the matrix hardness of the unirradiated samples of the scanning surface A series, and obtaining the hardness difference rate between the surface and the matrix of the unirradiated samples of the scanning surface A series; calculating according to the surface hardness of the irradiated samples of the scanning surface A series and the matrix hardness of the irradiated samples of the scanning surface A series, and obtaining the hardness difference rate between the surface and the matrix of the irradiated samples of the scanning surface A series; calculating according to the hardness difference rate between the surface and the matrix of the unirradiated samples of the scanning surface A series and the hardness difference rate between the surface and the matrix of the irradiated samples of the scanning surface A series, and obtaining the relative radiation hardening rate of the scanning surface A series. Among them, the relative radiation hardening rate of the scanning surface A series is the relative radiation hardening rate of the surfaces with different orientations.
[0088] Specifically, the hardness difference rate △H between the original unirradiated sample surface and the substrate of the scanning surface A series is calculated by formula (1): A,unirr , the hardness difference rate △H between the surface and the substrate of the irradiated sample of scanning surface A series is calculated by formula (2): A,irr , the relative radiation hardening rate R of the scanning surface A series is calculated by formula (3) A , as follows:
[0089]
[0090] R A =ΔH A,irr -ΔH A,unirr (3).
[0091] Step S106: Calculate according to the characteristic nanohardness value to obtain the relative radiation hardening rate of different deposition surfaces.
[0092] In the embodiment of the present invention, the relative radiation hardening rates of different deposition surfaces are obtained by calculation based on the characteristic nanohardness values, including: calculating based on the surface hardness of the non-irradiated samples of the deposition surface B series and the matrix hardness of the non-irradiated samples of the deposition surface B series to obtain the hardness difference rate between the surface and the matrix of the non-irradiated samples of the deposition surface B series; calculating based on the surface hardness of the irradiated samples of the deposition surface B series and the matrix hardness of the irradiated samples of the deposition surface B series to obtain the hardness difference rate between the surface and the matrix of the irradiated samples of the deposition surface B series; calculating based on the hardness difference rate between the surface and the matrix of the non-irradiated samples of the deposition surface B series and the hardness difference rate between the surface and the matrix of the irradiated samples of the deposition surface B series to obtain the relative radiation hardening rate of the deposition surface B series. Among them, the relative radiation hardening rate of the deposition surface B series is the relative radiation hardening rate of different deposition surfaces.
[0093] Specifically, the hardness difference rate △H between the original unirradiated sample surface and the substrate of the deposition surface B series is calculated by formula (1): B,unirrThe hardness difference rate △H between the surface of the B series irradiated samples and the substrate is calculated by formula (2): B,irr , the relative radiation hardening rate R of the deposition surface B series is calculated by formula (3) B , as follows:
[0094]
[0095] R B =ΔH B,irr -ΔH B,unirr (6).
[0096] Step S107: Calculate the relative radiation hardening rates of different oriented surfaces and the relative radiation hardening rates of different deposition surfaces to obtain anisotropy degree factors of the hardening effect.
[0097] In the embodiment of the present invention, R calculated according to formula (3) is A R calculated by formula (6) B , the anisotropy degree factor (X) of the hardening effect can be calculated. The anisotropy degree factor can be calculated by formula (7):
[0098]
[0099] Step S108: Evaluate the anisotropy degree of the object to be evaluated based on the anisotropy degree factor.
[0100] In the embodiment of the present invention, after the anisotropy factor X is calculated, the anisotropy factor X can be evaluated. Specifically, when X≤1, the material has basically no anisotropy at the microscopic level; when 1<X≤10, the anisotropy degree of the material at the microscopic level is low; when X>10, the anisotropy degree of the material at the microscopic level is high.
[0101] It can be understood that in the embodiment of the present invention, by repeating steps S101 to S108, the anisotropic effects of different additive materials can be compared, and the anisotropic degree factors of different materials can be calculated for comparison. The larger the anisotropic degree factor, the higher the anisotropy degree of the additive material.
[0102] refer to Figure 2 , Figure 2 This is a principle block diagram of the system for calculating and evaluating the degree of anisotropy of additive manufacturing materials provided by the present invention.
[0103] Specifically, Figure 2 As shown, the anisotropy degree calculation and evaluation system of additive manufacturing materials includes:
[0104] The sample preparation unit 201 is used to prepare an original sample based on the object to be evaluated; the object to be evaluated is a sample of additively manufactured nickel-based 718 alloy.
[0105] The irradiation unit 202 is used to select part of the original sample for irradiation to obtain irradiated samples.
[0106] The nanoindentation testing unit 203 is used to perform nanoindentation testing on non-irradiated samples and irradiated samples to obtain a relationship curve between indentation depth and nanohardness; the non-irradiated samples are samples of the original samples that have not been irradiated.
[0107] The characteristic value extraction unit 204 is used to extract characteristic nano-hardness values based on the relationship curve between the indentation depth and the nano-hardness to obtain characteristic nano-hardness values.
[0108] The first hardening rate calculation unit 205 is used to calculate according to the characteristic nanohardness value to obtain the relative radiation hardening rates of the surfaces with different orientations.
[0109] The second hardening rate calculation unit 206 is used to calculate according to the characteristic nanohardness value to obtain the relative radiation hardening rates of different deposition surfaces.
[0110] The anisotropy degree factor calculation unit 207 is used to calculate the anisotropy degree factor of the hardening effect according to the relative radiation hardening rates of different orientation surfaces and the relative radiation hardening rates of different deposition surfaces.
[0111] The anisotropy program evaluation unit 208 is used to evaluate the anisotropy degree of the object to be evaluated based on the anisotropy degree factor.
[0112] Specifically, the specific coordination operation process between the units in the additive manufacturing material anisotropy degree calculation and evaluation system here can refer to the above-mentioned additive manufacturing material anisotropy degree calculation and evaluation method, which will not be repeated here.
[0113] The present invention utilizes the difference in the degree of ion irradiation hardening of additively manufactured metal materials in different directions (characteristics of columnar crystal structure) and quantitatively evaluates anisotropy through the change law of hardness performance at the microscopic grain scale. The advantage of the method of the present invention is that compared with the conventional mechanical stretching method to evaluate macroscopic mechanical performance indicators such as yield, tensile strength, and elongation, the sample size required by this method is smaller, which is more suitable for small batches of materials or workpieces formed by SLM additive manufacturing, and can obtain relatively quantitative anisotropy evaluation indicators to evaluate additive molding technology, and help guide and optimize related material additive process technology.
[0114] The following is a description of a specific embodiment.
[0115] Specifically, the anisotropy degree of a nickel-based 718 alloy specimen manufactured by selective laser melting (SLM) additive manufacturing was calculated and evaluated.
[0116] 1) Sample preparation and processing: According to different orientation surfaces (scanning surface samples (A series) and deposition surface (B series)), square sheet samples with a thickness of 1 mm and a side length of 8 mm were processed by wire cutting. The sample surface was polished with 400-2000# metallographic sandpaper and then polished into a mirror surface;
[0117] 2) Ion irradiation: 540keV He irradiation was carried out on the polished surface of the sample in 1). 2+ In the ion irradiation experiment, the maximum depth of ion irradiation damage is 1 μm, and the irradiation damage is 1.0 dpa (the actual injection is 4.6×10 16 ions / cm 2 ), the irradiation temperature is room temperature.
[0118] 3) Nanoindentation test: Nanoindentation test in continuous stiffness mode was carried out on the unirradiated and irradiated samples, with Poisson's ratio of 0.3, indentation depth of 2 μm, and 10 test points for each sample. The average curve of the relationship between "indentation depth (nm, d)" and "nanohardness (GPa, H)" of the corresponding samples was obtained, as shown in Fig. Figure 3 shown.
[0119] 4) Characteristic nanohardness numerical extraction: According to the obtained dH relationship curve, 1 / d (μm -1 ) and H 2 (GPa 2 ), such as Figure 4 As shown, a segmented slope relationship curve is obtained, and 0μm is selected -1 ≤1 / d≤1μm -1 Linear fitting is performed on the area of the fitting line, and the square root H0 of the intercept of the fitting line is calculated to obtain the hardness of the matrix; 4μm is selected -1 ≤1 / d≤10μm -1 Linear fitting is performed on the area of , and the square root H1 of the intercept of the fitting line is calculated to obtain the surface hardness. According to this step, the calculation results are:
[0120] Scanning surface A series non-irradiated sample matrix hardness: H A0,unirr =3.653GPa;
[0121] Scanning surface A series unirradiated sample surface hardness: H A1,unirr =4.583GPa;
[0122] Scanning surface A series irradiated sample matrix hardness: H A0,irr =3.316GPa;
[0123] Scanning surface A series irradiated sample surface hardness: H A1,irr =5.838GPa;
[0124] Deposition surface B series non-irradiated sample matrix hardness: H B0,unirr =3.584GPa;
[0125] Surface hardness of unirradiated samples of series B on the deposition surface: H B1,unirr =4.655GPa;
[0126] Deposition surface B series irradiated sample matrix hardness: H B0,irr =3.534GPa;
[0127] Surface hardness of B series irradiated samples on the deposition surface: H B1,irr =5.841GPa.
[0128] 5) Calculate the hardness difference rate △H between the original unirradiated sample surface and the substrate of the scanning surface A series by formula (1): A,unirr , the hardness difference rate △H between the surface and the substrate of the irradiated sample of scanning surface A series is calculated by formula (2): A,irr , and then calculate the relative radiation hardening rate R of the scanning surface A by formula (3) A .
[0129] △H A,uirr =(H A1,unirr -H A0,unirr ) / H A0,unirr ×100%=25.5%;
[0130] △H A,irr =(H A1,irr -H A0,irr ) / H A0,irr ×100%=76.1%;
[0131] R A =△H A,irr -△H A,uirr =50.6%.
[0132] 6) Calculate the hardness difference between the original unirradiated sample surface and the substrate of the deposition surface B series by formula (4): B,unirr The hardness difference rate △H between the surface and the substrate of the B series irradiated sample is calculated by formula (5): B,irr , and then the relative radiation hardening rate R of the deposition surface B is calculated by formula (6) B .
[0133] △H B uirr =(H B1,unirr –H B0,unirr) / H B0,unirr ×100%=29.9%;
[0134] △H B,irr =(H B1,irr –H B0,irr ) / H B0,irr ×100%=65.3%;
[0135] R B =△H B,irr -△H B,uirr =35.4%.
[0136] 7) Based on the degree of radiation hardening, the "anisotropy factor X" of the hardening effect is calculated using Formula 7, and the degree of anisotropy is evaluated.
[0137]
[0138] Since X>10, it indicates that the anisotropy of the additively manufactured 718 material is relatively high at the microscopic level.
[0139] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0140] Professionals may further appreciate that the units and algorithm steps of each example described in conjunction with the embodiments disclosed herein can be implemented in electronic hardware, computer software, or a combination of the two. In order to clearly illustrate the interchangeability of hardware and software, the composition and steps of each example have been generally described in the above description according to function. Whether these functions are performed in hardware or software depends on the specific application and design constraints of the technical solution. Professionals and technicians may use different methods to implement the described functions for each specific application, but such implementation should not be considered to be beyond the scope of the present invention.
[0141] The steps of the method or algorithm described in conjunction with the embodiments disclosed herein may be implemented directly using hardware, a software module executed by a processor, or a combination of the two. The software module may be placed in a random access memory (RAM), a memory, a read-only memory (ROM), an electrically programmable ROM, an electrically erasable programmable ROM, a register, a hard disk, a removable disk, a CD-ROM, or any other form of storage medium known in the art.
[0142] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot limit the scope of protection of the present invention. All equivalent changes and modifications made to the scope of the claims of the present invention should fall within the scope of the claims of the present invention.
Claims
1. A method for calculating and evaluating the degree of anisotropy of additive manufacturing materials, characterized in that: The following steps are involved: Prepare an original sample based on an object to be evaluated; the object to be evaluated is an additively manufactured nickel-based 718 alloy; Selecting a portion of the original sample for irradiation to obtain an irradiated sample; Nanoindentation tests were performed on non-irradiated samples and irradiated samples to obtain the relationship curve between indentation depth and nanohardness; The non-irradiated sample is a sample of the original sample that has not been irradiated; Extract characteristic nanohardness values based on the relationship curve between the indentation depth and the nanohardness to obtain characteristic nanohardness values; Calculating according to the characteristic nanohardness value, obtaining the relative radiation hardening rate of the surfaces with different orientations; Calculating according to the characteristic nanohardness values, obtaining relative radiation hardening rates of different deposition surfaces; Calculating according to the relative radiation hardening rates of the different oriented surfaces and the relative radiation hardening rates of the different deposition surfaces to obtain an anisotropy degree factor of the hardening effect; The anisotropy degree of the object to be evaluated is evaluated based on the anisotropy degree factor.
2. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 1, characterized in that: The preparation of the original sample based on the object to be evaluated comprises: The object to be evaluated is subjected to wire cutting processing according to different orientation surfaces and deposition surfaces to obtain square sheet samples; The surface of the square plate sample is ground and polished to obtain the original sample.
3. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 1, characterized in that: The selecting part of the original samples for irradiation to obtain irradiated samples comprises: Selecting some samples from the original sample; The polished surfaces of the partial samples are subjected to ion irradiation to obtain the irradiated samples.
4. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 1, characterized in that: The maximum depth of ion irradiation damage of the irradiated sample is 1 μm to 1.5 μm, the irradiation operation amount is 1.0 dpa, and the irradiation temperature is room temperature.
5. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 1, characterized in that: The nanoindentation test is performed on the non-irradiated sample and the irradiated sample to obtain the relationship curve between the indentation depth and the nanohardness, including: The non-irradiated sample and the irradiated sample are subjected to a nanoindentation test in a continuous stiffness mode to obtain a relationship curve between the indentation depth and the nanohardness.
6. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 5, characterized in that: The test conditions of the nanoindentation test are: Poisson's ratio is 0.3, the indentation depth is 2 μm, and the number of test points for each sample is not greater than or equal to 10.
7. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 1, characterized in that: The extracting of characteristic nanohardness values based on the relationship curve between the indentation depth and the nanohardness to obtain the characteristic nanohardness values comprises: Based on the relationship curve between the indentation depth and the nanohardness, a relationship curve of the segmented slope is obtained; Determine the first selected area; Performing linear fitting on the relationship curve of the segmented slopes based on the first selected area to obtain a first fitting straight line; Calculating the arithmetic square root of the intercept of the first fitting straight line to obtain the hardness of the substrate; Determine the second choice area; Performing linear fitting on the relationship curve of the segmented slopes based on the second selected area to obtain a second fitting straight line; Calculating the arithmetic square root of the intercept of the second fitting straight line to obtain the hardness of the surface; The hardness of the substrate and the hardness of the surface are the characteristic nanohardness values.
8. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 1, characterized in that: The characteristic nano-hardness values include: the hardness of the substrate and the hardness of the surface; The hardness of the substrate includes: the substrate hardness of the unirradiated samples of the scanning surface A series, the substrate hardness of the irradiated samples of the scanning surface A system, the substrate hardness of the unirradiated samples of the deposition surface B series, and the substrate hardness of the irradiated samples of the deposition surface B system; The surface hardness includes: the surface hardness of the unirradiated samples of the scanning surface A series, the surface hardness of the irradiated samples of the scanning surface A system, the surface hardness of the unirradiated samples of the deposition surface B series, and the surface hardness of the irradiated samples of the deposition surface B system.
9. The method for calculating and evaluating the anisotropy degree of additive manufacturing materials according to claim 8, characterized in that: The step of calculating according to the characteristic nanohardness value to obtain the relative radiation hardening rate of different oriented surfaces includes: Calculating according to the surface hardness of the unirradiated samples of the scanning surface A series and the matrix hardness of the unirradiated samples of the scanning surface A series, to obtain the hardness difference rate between the surface and the matrix of the unirradiated samples of the scanning surface A series; Calculate the hardness difference between the surface and the substrate of the irradiated samples on the scanning surface A series according to the surface hardness of the irradiated samples on the scanning surface A series and the substrate hardness of the irradiated samples on the scanning surface A series to obtain the hardness difference between the surface and the substrate of the irradiated samples on the scanning surface A series; The relative radiation hardening rate of the scanning surface series A is obtained by calculating the hardness difference rate between the surface of the unirradiated sample and the substrate and the hardness difference rate between the surface of the irradiated sample and the substrate of the scanning surface series A; the relative radiation hardening rate of the scanning surface series A is the relative radiation hardening rate of the surfaces with different orientations; The calculation according to the characteristic nanohardness value to obtain the relative radiation hardening rate of different deposition surfaces includes: Calculate the hardness difference between the surface and the substrate of the non-irradiated samples of the deposition surface B series according to the surface hardness of the non-irradiated samples of the deposition surface B series and the substrate hardness of the non-irradiated samples of the deposition surface B series to obtain; Calculate the hardness difference between the surface and substrate of the B series irradiated samples on the deposition surface according to the surface hardness of the B series irradiated samples on the deposition surface and the substrate hardness of the B series irradiated samples on the deposition surface to obtain the hardness difference between the surface and substrate of the B series irradiated samples on the deposition surface; The relative irradiation hardening rate of the deposition surface series B is obtained by calculating the hardness difference rate between the surface of the non-irradiated samples of the deposition surface series B and the substrate and the hardness difference rate between the surface of the irradiated samples of the deposition surface series B and the substrate; The relative radiation hardening rates of the deposition surfaces B series are the relative radiation hardening rates of the different deposition surfaces.
10. A system for calculating and evaluating the degree of anisotropy of additive manufacturing materials, characterized in that: include: A sample preparation unit, used for preparing an original sample based on an object to be evaluated; The object to be evaluated is a sample of additively manufactured nickel-based 718 alloy; An irradiation unit, used for selecting a portion of the original sample for irradiation to obtain an irradiated sample; Nanoindentation test unit, used to perform nanoindentation test on non-irradiated samples and irradiated samples to obtain the relationship curve between indentation depth and nanohardness; The non-irradiated sample is a sample of the original sample that has not been irradiated; A characteristic value extraction unit, used to extract characteristic nanohardness values based on the relationship curve between the indentation depth and the nanohardness, and obtain characteristic nanohardness values; A first hardening rate calculation unit, used to calculate according to the characteristic nanohardness value to obtain relative radiation hardening rates of surfaces with different orientations; A second hardening rate calculation unit, used to calculate according to the characteristic nanohardness value to obtain relative radiation hardening rates of different deposition surfaces; an anisotropy degree factor calculation unit, used to calculate the anisotropy degree factor of the hardening effect according to the relative radiation hardening rates of the different orientation surfaces and the relative radiation hardening rates of the different deposition surfaces; The anisotropy program evaluation unit is used to evaluate the anisotropy degree of the object to be evaluated based on the anisotropy degree factor.
Citation Information
Patent Citations
Micro-nano mechanical testing method for anisotropy of two-dimensional functional material
CN115046817A
Device and method for forming isotropic continuous fiber reinforced composite material
CN115782163A
Aluminum alloy and quality control method of aluminum alloy
CN118275480A
Component control and preparation method of high-toughness isotropic additive manufacturing 316L stainless steel
CN118341987A
Additive manufacture of anisotropic rare earth magnets
US20200094321A1